Cognitive, motor and non-planner impulsiveness in reactive, proac-tive and mixed aggressive adolescents - Andreu-Rodríguez, Jose M.; Peña, María E.; Penado, María (Anales de Psicología / Annals of Psychology, 2013)
This paper focuses on the study of impulsiveness in a sample of adolescents with different types of aggression. The main research objective was to analyze whether impulsiveness varies between different aggressive adolescents (reactive, proactive and mixed) and non-aggressive ones. Two self-report measures, the Reactive and Proactive Aggression Questionnaire (RPAQ) and the Barratt Impulsiveness Scale (BIS-11) were administrated in a sample recollected in Madrid and composed by 400 adolescents between 12 and 18 years of age (mean = 14.8 and SD = 1.8). The results showed that reactive, proactive and mixed aggressive groups presented higher levels of general impulsiveness than nonaggressive adolescents. No significant differences in relation to cognitive and non-planner dimensions of impulsiveness were found. Nevertheless, motor impulsiveness was higher in reactive, proactive and mixed aggressive adolescents in comparison with non-aggressive ones. These results are discussed pointing out the relevance of motor impulsiveness as a discriminative factor of aggression, particularly in the context of psychological intervention with adolescents in scholar settings